Ramadan Risk Stratification by International Diabetes Federation and Diabetes & Ramadan International Alliance (IDF-DAR) Risk Calculator in Bangladeshi People with Diabetes Mellitus who wished to Fast in 2022 (Journal of Rangpur Medical College, 2022)
Background: Risk stratification is an essential and first component of the pre-Ramadan assessment of patients with diabetes mellitus (DM) who wish to fast. Limited data are reported from Bangladesh regarding risk stratification of people with DM who wish to fast.Objective: To determine the risk status of people with DM who wish to fast during Ramadan.Methods: This cross-sectional observational study was done among Muslim people of DM with at least one year of experience of Ramadan in previous years after their diagnosis. Along with baseline characteristics, the individual 14 risk elements of the International Diabetes Federation and Diabetes & Ramadan International Alliance (IDF-DAR) risk calculator- 2021 were assessed. Patients were categorized into low, moderate, and high risk with a total score of 0-3, 3.5-6, and ≥6.5 respectively. Moderate and high-risk patients were counseled about their risk of fasting and requested to reconsider their wishes.Results: Among 569 participants, (mean age 50.97±12.02 years, male-female ratio 36.2:63.8) 37.8%, 38.8%, and 23.4% had high, moderate, and low risk respectively. Risk scores were significantly higher in older age (p